Case report: Movement analysis in oncological rehabilitation: proposal of a kinematic and surface electromyographic protocol in breast oncology - Bongiorno, Giulia; Tomasi, Andrea; Vigni, Giulio; Rizzardo, Alessandro; Biancuzzi, Helena; Dal Mas, Francesca; Bednarova, Rym; Miceli, Luca (Frontiers in Human Neuroscience, 2024)
Breast cancer disease often affects the ipsilateral shoulder joint, with pain and joint limitation. Proper pain management, which can be obtained for example using pulsed radiofrequency of the suprascapular nerve, can help the physiotherapist along his path. The modern technologies of kinematic analysis and 2 This is a provisional file, not the final typeset article surface electromyography of movement analysis can give further support in building a personalized rehabilitation program, based on the quantitative study of movement, in this case of the upper limb. This brief report aims to develop and test the evolution of a shoulder joint analysis protocol based on an inertial accelerometer and non-invasive surface electromyography. An analysis algorithm was therefore created capable of adapting to the needs of women operated on at the breast based on a kinematic component (ROM -range of movement -and Jerk index) and an electromyographic one (study of muscle behavior in groups of four). The coactivations were also evaluated, both as an average value and in graphical form, to offer the physiotherapist a complete overview of the movement of the upper limb. The strength of this protocol is its simplicity of use, combined with the reduced time required for processing the reports and the portability of the PC-sensors complex, making these analyzes potentially bedside for the patient.